Levels of bioelements and their relation to the ruminants ' needs in the most important pasture-plant species of the wooded dehesa ( grazing-land ) in the south-west of Spain (Dynamics and sustainability of Mediterranean pastoral systems . CIHEAM, (Cahiers Options Méditerranéennes; n. 39), 1999)
- The Trifolium subterraneum and Orithopus compressus species, together are considered the most important pasture plants (pratenses) with the gramineae group of the wooded 'dehesa' of Edremadura. In the present paper 5 representative "dehesas" (pasture lands) of the south-west of the province of Badajoz (200,000 ha) are studied over a period of two agricultural years (1 993-94 and 94-95). Soils and plants were analysed every fortnight approximately, from Autumn until the end of Spring. Samples of plants from the different plots were taken to check the proportions of N, P, K, Ca and Mg. Climatologically two different weather conditions were studied, a year of almost average rainfall and another of extreme drought. The minimum values for these 5 elements were revised. The Nitrogen proportion in both leguminous species was above the required minimum level (even in dry grass), for the ruminant feeding (over 1.5% and up to 3.5% in January and February), whereas there was a deficiency of Nitrogen in the gramineae group from April on. Regarding Phosphorus, as the plant becomes mature a decrease is noted, which was stressed in the final months of the cycle; all the dehesas studied except Manpolín reached lower rates than the minimum required (0.20%). The potassium evolved in a similar way that of P, although deficiencies (minimum 0.60%) arose only in Campos de Oliva. Its behaviour was similar in both years. Calcium had a similar behaviour in all the dehesas studied along the vegetative cycle. It was always above the minimum level (0.30%) in the gramineae from April on in both years. Magensium results were similar to those of Calcium